Child soldiers in Africa - Honwana, Alcinda Manuel (Ethnography of political violence., 2006)
In Child Soldiers in Africa Alcinda Honwana brings her firsthand experience with child soldiers in Angola and Mozambique to shed light on how children are recruited, what they encounter, and how they come to terms with what they have done.